ORGANISATIONAL JUSTICE, ORGANISATIONAL VIRTUOUSNESS AND PERFORMANCE AMONG BANK EMPLOYEES - Manikandan. K and Anipriya. S (SJBIR: SAARJ Journal on Banking & Insurance Research, 2014)
The present study tries to explore the association of organizational justice, organizational virtuousness and performance of bank employees in Kerala in a positive psychological perspective. The participants of this study were bank employees who are working in either government or private banks in Kerala. The instruments used were Calicut University Virtuousness Scale, Organizational Justice Questionnaire and Performance Rating Scale. The study employed factorial designs to test the hypotheses. The study revealed that organizational virtuousness, procedural justice and distributive justice have a significant correlation with performance. Females were found to have more procedural justice, distributive justice and organizational virtuousness and also no significant difference exist in the performance, procedural justice, distributive justice and organizational virtuousness among people working both in private and public sector.